2016
DOI: 10.3892/or.2016.4681
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Runt-related transcription factor 3 induces resistance to 5-fluorouracil and cisplatin in hepatocellular carcinoma

Abstract: Runt-related transcription factor 3 (RUNX3) is known to function as a tumor suppressor in gastric cancer and other types of cancers, including hepatocellular carcinoma (HCC). However, its role has not been fully elucidated. In the present study, we aimed to evaluate the role of RUNX3 in HCC. We used the human HCC cell lines Hep3B, Huh7 and HLF; RUNX3 cDNA was introduced into Hep3B and Huh7 cells, which were negative for endogenous RUNX3 expression, and RUNX3 siRNA was transfected into HLF cells, which were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Patients with HCC initially respond to cisplatin therapy but resistance frequently occurs, which is associated with increased DNA repair, altered cell accumulation and increased drug efflux mediated by multidrug resistance proteins (20). It has been reported that cisplatin resistance in HCC may occur through the loss of Runt-associated transcription factor 3 and upregulation of cyclophilin B (21,22). Recently, certain key biomarkers of cisplatin resistance have revealed novel molecular mechanisms of resistance (23).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HCC initially respond to cisplatin therapy but resistance frequently occurs, which is associated with increased DNA repair, altered cell accumulation and increased drug efflux mediated by multidrug resistance proteins (20). It has been reported that cisplatin resistance in HCC may occur through the loss of Runt-associated transcription factor 3 and upregulation of cyclophilin B (21,22). Recently, certain key biomarkers of cisplatin resistance have revealed novel molecular mechanisms of resistance (23).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, genes with this structure are highly susceptible to be regulated by methylation. 4,5 DNA methylation is an epigenetic modification that regulates the gene expression and provides a mechanism for conveying and preserving epigenetic information through DNA replication and cell division. Accumulating studies have indicated that aberrant changes in DNA methylation are amongst the most common molecular alterations associated with tumorigenesis and hypermethylation of the promoter region of various cancer suppressor genes is recognized as one of the most frequent mechanisms for loss of gene function.…”
Section: Introductionmentioning
confidence: 99%
“…We identified the most likely targets of miR‐335‐5p as CDC42, CDK2, CSNK1G2, EIF2C2, EIF5, LIMK1, NRG1, PLK2, RGS19, TCF3, THBS1, YBX1, and ZMYND8. Among these genes, CDC 42, CDK2, EIF2C2, EIF5, LIMK1, NRG1, PLK2, RGS19, TCF3, THBS1, as well as YBX1 have been implicated in hepatocellular carcinoma, and some of them are related to invasion and metastasis. Out of these 13 downstream miR‐335‐5p targets, CSNK1G2 and ZMYND8 are reported here for the first time as playing a role in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…We identified the most likely targets of miR-335-5p as CDC42 (Cell division control protein 42 homolog), CDK2 (Cyclin-dependent kinase 2), CSNK1G2 (Casein kinase 1 gamma 2), EIF2C2 (Protein argonaute-2), EIF5 (Eukaryotic translation initiation factor-5), LIMK1 (LIM Domain Kinase 1), NRG1 (Neuregulin 1), PLK2 (Polo Like Kinase 2), RGS19 (G-protein signaling 19), TCF3 (Transcription Factor 3), THBS1 (Thrombospondin 1), YBX1 (Y-Box Binding Protein 1) and ZMYND8 (human Zinc Finger MYND-type containing 8). Among these genes, CDC 42(19, 20), CDK2(21, 22), EIF2C2(23, 24), EIF5(25, 26), LIMK1(27), NRG1(28), PLK2(29), RGS19(30), TCF3(31), THBS1(32) as well as YBX1(33) have been implicated in hepatocellular carcinoma, and some of them are related to invasion and metastasis. Out of these 13 downstream miR-335-5p targets, CSNK1G2 and ZMYND8 are reported here for the first time as playing a role in HCC.…”
Section: Discussionmentioning
confidence: 99%